The NETS Project: A NEtwork of transit surveys - Jiang, I.-G. (EPJ Web of conferences, 2011)
Motivated by the recent quick and successful development in the searching extrasolar planet (exoplanet) by transit events, I started an instrumental project, the NETS Project, in 2006. In this paper, the background, goal, our design, the progress, and the current status will be reviewed. Although our research grant and manpower are limited, we are approaching to the stage to build up a station at an astronomical observatory.